Trust and Risk in Games of Partial Information - Robin Clark (Baltic International Yearbook of Cognition, Logic and Communication, 2013)
Games of partial information have been used to explicate Gricean implicature; their solution concept has been murky, however. In this paper, I will develop a simple solution concept that can be used to solve games of partial information, depending on the players' mutual trust and tolerance for risk. In addition, I will develop an approach to non-conventional quantity implicatures that relies on "face" (Goffman (1967), Brown and Levinson (1987)).
Keywords: game theory; logic; partial information